Assessment of turbulent flow effects on the vessel wall using four‐dimensional flow MRI. Issue 6 (28th June 2016) - Ziegler, Magnus; Lantz, Jonas; Ebbers, Tino; Dyverfeldt, Petter
Abstract : Purpose: To explore the use of MR‐estimated turbulence quantities for the assessment of turbulent flow effects on the vessel wall. Methods: Numerical velocity data for two patient‐derived models was obtained using computational fluid dynamics (CFD) for two physiological flow rates. The four‐dimensional (4D) Flow MRI measurements were simulated at three different spatial resolutions and used to investigate the estimation of turbulent wall shear stress (tWSS) using the intravoxel standard deviation (IVSD) of velocity and turbulent kinetic energy (TKE) estimated near the vessel wall. Results: Accurate estimation of tWSS using the IVSD is limited by the spatial resolution achievable with 4D Flow MRI. TKE, estimated near the wall, has a strong linear relationship to the tWSS (mean R 2 = 0.84). Near‐wall TKE estimates from MR simulations have good agreement to CFD‐derived ground truth (mean R 2 = 0.90). Maps of near‐wall TKE have strong visual correspondence to tWSS. Conclusion: Near‐wall estimation of TKE permits assessment of relative maps of tWSS, but direct estimation of tWSS is challenging due to limitations in spatial resolution. Assessment of tWSS and near‐wall TKE may open new avenues for analysis of different pathologies. Magn Reson Med 77:2310–2319, 2017. © 2016 International Society for Magnetic Resonance in Medicine